Case report: A decade-long journey with cyclic thrombocytopenia - Al-Assil, Talal; Ellythy, Suhaib; Idris, Omer A.; Omaira, Mohammad (Frontiers in Hematology, 2025)
Cyclic thrombocytopenia (CTP) is a rare hematological disorder characterized by significant oscillations in platelet counts, alternating between phases of severe thrombocytopenia and periods of normal or elevated platelet levels. Due to its clinical similarities with Immune Thrombocytopenia (ITP), CTP presents a diagnostic challenge. We report the case of a 54-year-old woman who first presented at age 45 with a petechial rash, heavy menstruation, and severe thrombocytopenia with a platelet count of less than 5,000 × 10^9/L. Her severe thrombocytopenia was followed by marked rebound thrombocytosis, ultimately leading to a clinical diagnosis of idiopathic cyclic thrombocytopenia (CTP). Unlike other cyclic hematological disorders, CTP exclusively affects platelet counts distinguishing it from other conditions. It is unresponsive to conventional ITP treatments, and thus accurate diagnosis through vigilant platelet monitoring in unexplained thrombocytopenia can help CTP patients avoid unnecessary therapies and their associated side effects.